Creative Writing for Critical Thinking Creating a Discoursal Identity - Edberg, Hélène (Springer International Publishing, 2018)
This book explores narrative imagination and emotion as resources for learning critical meta-reflection. The author examines the learning trajectories of several students as they engage in learning to think critically through a new approach to creative writing, and details how learning through writing is linked to new discoursal identities which are trialled in the writing process. In doing so, she analyses the processes of expansion and change that result from the negotiations involved in learning through writing. This volume offers a completely new approach to creative writing, including useful practical advice as well as a solid theoretical base. It is sure to appeal to students of creative writing and discourse analysis as well as applied linguistics and language as identity. Hélène Edberg is Senior Lecturer and Educational Developer at Södertörn University, Sweden. Her research interests are based around applied linguistics and rhetoric. She has been tea ching creative writing for over a decade, and is particularly interested in identification processes linked to learning through writing. .